Absolute configuration determination of SMTP-7 via microcrystal electron diffraction (MicroED). Issue 94 (28th October 2022) - Wang, Bo; Lin, Yiqing
Abstract : The absolute configuration of a clinically important drug candidate, SMTP-7, with only micron-sized powders available, is directly obtained via microcrystal electron diffraction (MicroED) analysis. Abstract : Direct absolute configuration determination of a drug candidate bearing five chiral centers, SMTP-7, is lacking. With only few-micron-sized powders available, we assigned the absolute configuration of SMTP-7 via MicroED analysis through kinematical refinement with additional chiral information and directly through the recently developed dynamical refinement approach. We showcased the utility of the latest advance in MicroED to unambiguously assign absolute configuration for hard-to-crystallize, complex, and quantity-limited molecules.